Evolution and current approaches in brest and axillary surgery for the treatment of early breast cancer - González-Burgos, Dario (2025)
This article reviews the evolution of the surgical treatment of breast cancer, from radical mastectomy to extremeoncoplastic surgery. Through this progression, radical axillary dissection has also been substantially transformed. Therefore,we present the de-escalation process of axillary dissection, highlighting sentinel lymph node biopsy as the most widely accepted standard of care in cases with clinically negative nodes and negative sentinel nodes. This is because it has demonstrated comparable outcomes in terms of disease-free survival, overall survival, and low local recurrence rates when comparing axillary dissection with sentinel lymph node biopsy alone in randomized patient groups. Additionally, recent studies show that axillary dissection after neoadjuvant therapy and radiotherapy may be omitted in specific cases of patients with clinically positive nodes or positive sentinel nodes. Lastly, there is ongoing research exploring the potential to omit sentinel lymph node biopsy by combining neoadyuvant therapy, radiotherapy and preoperative ultrasound assessment. These findings underline the relevance of individualized and multidisciplinary decision making to tailor treatment for each patient. The movement towards the oncoplastic surgery and a less invasive axillary intervention is supported, aiming to reduce morbidity and complications, thus improving patients' quality of life. Further studies are required to continue assessing the efficacy of less invasive approaches.